Cover Feature: Interactions of Ascorbic Acid with Satraplatin and its trans Analog JM576: DFT Computational Study (Eur. J. Inorg. Chem. 13/2018) - Šebesta, Filip; Burda, Jaroslav V. (European journal of inorganic chemistry, 2018)
The Cover Feature shows the theoretical possibility that a satraplatin–platinum(IV) complex can be reduced by ascorbic acid in a cellular environment. According to the performed calculations, the transfer of two electrons from ascorbic acid to the platinum(IV) complex can occur spontaneously especially under pH 7. The reduced platinum(II) metabolite is generally accepted to be an active metallodrug, which can make intra‐strand cross‐links responsible for triggering the apoptotic process. More information can be found in the Full Paper by F. Šebesta and J. V. Burda.